Malawi CAADP bienniel review brief: Africa agriculture scorecard performance and lessons - Musopole, Readwell; Mwanaleza, Emmanuel; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Nhemachena, Charles; Nkhoma, Dominic (International Food Policy Research Institute, 2019)
The objective of this brief is to present Malawi’s performance and discuss lessons from the implementation of the inaugural CAADP BR mechanism. Based on the results, recommendations are proposed to help strengthen mutual accountability on actions and results and the performance of the agriculture sector in Malawi. The analysis is based on a review of the results of the inaugural BR report and Africa Agriculture Transformation Scorecard (AATS) that were presented to African Heads of State and Government in January 2018. Additional information was analysed using technical notes in the Malawi country BR report. Experiences and lessons from continental and regional engagements in the implementation of the BR process were also integrated into the analysis.